Ação da pentoxifilina na vitalidade e no reparo tecidual dos retalhos cutaneos em ratos, administrada via subcutânea - Stephanie Luzia da Costa Pedretti (2019)
Introduction: the skin flaps play a very important role of the plastic surgery for the reconstruction of tissue loss, but may present complications such as ischemia and necrosis. Objectives: To verify the action of pentoxifylline, administered by subcutaneous route, at the dose of 100 mg / kg, in the vitality and tissue repair in cutaneous flaps of rats. To identify histological elements, such as number of vessels, ephithelium thickness, density of collagen and dosages of VEGF and TGF-β-1. Method: 32 Wistar rats (Rattus Norvegicus albinus), distributed in four groups named CT, P1, P3, P5, with eight animals each, were used. The modified Mcfarlane skin flap, caudal pedicle was performed. In the CT group the flap received gauze soaked with saline on the flap bed. Pentoxifylline was administered, by subcutaneous route, in the P1, P3, P5 groups, in the perioperative until the 5th postoperative day. Macroscopic variables were measured: total flap size, tissue with necrosis and tissue viability. The excision of the flap was performed for histological analysis and biochemical measurements of VEGF and TGF-β1. The animals were submitted to euthanasia on the 10th day. Morphometric analyzes quantified: number of vessels, epithelium thickness and collagen density. Results: The macroscopic analysis of the rat skin flap showed that the mean tissue size with necrosis in the CT group was 35.85 mm (± 1.95) and in the P5 group: 22.73 mm (± 0.87), p <0.0001. The size of the viable tissue in the groups, CT: 39.2mm (± 1.62) and P5: 45.85mm (± 0.8074), p = 0.0164. The morphometric analysis showed that the number of vessels / field increased in the three segments of the skin flap with significant diferences, in the distal segment of the flapin groups, CT : 21 (± 3.4) and P5: 40 (± 5.0), p = 0.0174. The epithelium thickness of the increased in the three segments of the skin. In the distal segment, CT group: 9μm (± 0.5), P5 group: 15μm (± 1.1), p <0.0001. The collagen density decreased in all segments of the cutaneous flap in the treated groups. In the distal segment, CT group: 138000μm2 (± 3330), P5 group: 34430μm2 (± 5321), p <0,0001. The levels of VEGF in the skin samples of the CT group: 246.8pg / mg (± 25.8), P5 group: 471.1pg / mg (± 33.8), p <0.0001. In the sérum, CT group: 145.2pg / mg (± 5.1), P5 group: 223.9pg / mg (± 25.2), p = 0.005. The levels of TGF-β1 in the skin samples of the CT group: 162.1 pg / mg (± 22.9), P5 group: 46.4 pg / mg (± 17.20), p = 0.018. In the sérum, group CT: 313.9 pg / mg (± 28.5), P5 group: 191.3 pg / mg (± 15.9), p = 0.0063. Conclusion: Pentoxifylline administered by subcutaneous route, increased vitality and repair of cutaneous flaps in the groups of rats treated for a greater number of days. There was an increase a number of vessels VEGF, and epithelial thickness. Evident decreased collagen density and TGF-β1.